PENGARUH PEMASARAN MEDIA SOSIAL DAN PERAN PEMENGARUH TERHADAP KEPUTUSAN PEMBELIAN LABUBU - Chelsea Gracia; Surianto (Pojok Publisher, 2025)
The marketing industry increasingly integrates diverse elements to enhance its impact on various corporate objectives. Across sectors, companies have adopted social media as a strategic platform for executing marketing initiatives, complemented by the utilization of influencers to bolster message credibility. This study aims to examine the relationship and contributory influence of social media marketing and influencer engagement on consumer purchase decisions. The research focuses on the Labubu brand, which experienced a significant surge in purchases during 2024. Data were collected through structured questionnaires completed by 97 respondents who met the defined sample characteristics. The study was conducted in Jakarta, targeting individuals who had made purchasing decisions regarding Labubu products. The findings reveal that both social media marketing and influencer involvement individually exert a statistically significant positive effect on purchasing decisions. Moreover, when considered concurrently, these variables jointly contribute a significant positive influence on consumers' decisions to purchase Labubu-branded products.